Expression 41: "y" minus 0.9 equals negative left parenthesis, 0.1 7 6 "x" plus left parenthesis, negative ( 4.6 7 "x" minus 20 ) to the 10000 power , right parenthesis , right parenthesis left brace, 4.4 9 6 7 6 greater than "x" greater than 4.0 6 8 5 5 , right bracey−0.9=−0.176x+−(4.67x−20)100004.49676>x>4.06855
41
Expression 42: ( ( negative ( "x" minus 0.5 minus 2.8 7 5 ) ) ) Superscript, 1 sixth , Baseline equals left parenthesis, "y" minus 1.7 5 , right parenthesis / 1.5 9 left brace, 2.8 7 5 less than "x" less than 3.3 7 5 , right brace((−(x−0.5−2.875)))16=y−1.75/1.592.875<x<3.375
42
Expression 43: ( ( ( "x" plus 0.5 minus 2.8 7 5 ) ) ) Superscript, 1 sixth , Baseline equals left parenthesis, "y" minus 1.7 5 , right parenthesis / 1.5 9 left brace, 2.3 7 5 less than "x" less than 2.8 7 5 , right brace(((x+0.5−2.875)))16=y−1.75/1.592.375<x<2.875
43
Expression 44: "y" minus 5.9 7 6 equals negative ( 2.0 5 4 squared minus "x" squared ) Superscript, .5 , Baseline left brace, 2 less than "x" less than 2.0 5 4 , right bracey−5.976=−(2.0542−x2).52<x<2.054
44
Expression 45: "y" minus 5.9 7 6 equals negative ( 2.0 5 4 squared minus "x" squared ) Superscript, .5 , Baseline left brace, negative 2 greater than "x" greater than negative 2.0 5 4 , right bracey−5.976=−(2.0542−x2).5−2>x>−2.054
45
Expression 46: "y" minus 5.9 7 6 equals ( 2.0 5 4 squared minus "x" squared ) Superscript, 0.5 , Baseliney−5.976=(2.0542−x2)0.5
46
Expression 47: "y" equals 4.7 left brace, negative 2 less than "x" less than 2 , right bracey=4.7−2<x<2
47
Expression 48: "y" equals 4.9 left brace, negative 2 less than "x" less than 2 , right bracey=4.9−2<x<2
48
Expression 49: "y" equals 3.7 left brace, 2 less than "x" less than 3.7 , right bracey=3.72<x<3.7
49
Expression 50: "y" equals 3.7 left brace, negative 3.7 less than "x" less than negative 2 , right bracey=3.7−3.7<x<−2
50
Expression 51: "y" equals 4.6 left brace, negative 2 less than "x" less than 2 , right bracey=4.6−2<x<2
51
Expression 52: "y" equals 0.1 7 6 ( negative "x" plus 3.7 ) plus 3.7 left brace, 3.7 less than "x" less than 4.8 , right bracey=0.176(−x+3.7)+3.73.7<x<4.8
52
Expression 53: "y" equals 0 left brace, negative 9.9 less than "x" less than 9.9 , right bracey=0−9.9<x<9.9
53
Expression 54: negative 1.4 5 less than or equal to "x" less than or equal to negative 1.1 5 left brace, 0 less than "y" less than 3.8 , right brace−1.45≤x≤−1.150<y<3.8
54
Expression 55: 1.4 5 greater than or equal to "x" greater than or equal to 1.1 5 left brace, 0 less than "y" less than 3.8 , right brace1.45≥x≥1.150<y<3.8
55
Expression 56: 3.5 2 less than or equal to "y" less than or equal to 3.7 9 left brace, negative 1.1 5 less than "x" less than 1.1 5 , right brace3.52≤y≤3.79−1.15<x<1.15
56
Expression 57: "x" equals 0.5 left brace, 0 less than "y" less than 1 , right bracex=0.50<y<1
57
Expression 58: "x" equals negative 0.5 left brace, 0 less than "y" less than 1 , right bracex=−0.50<y<1
58
Expression 59: "y" equals 1 left brace, negative 0.5 less than "x" less than 0.5 , right bracey=1−0.5<x<0.5
59
Expression 60: "x" equals 0 left brace, 0 less than "y" less than 1 , right bracex=00<y<1
60
Expression 61: "x" equals negative 10 left brace, 0 less than "y" less than 9 , right bracex=−100<y<9
61
Expression 62: "x" equals negative 9 left brace, 0 less than "y" less than 9 , right bracex=−90<y<9
62
Expression 63: "y" equals 9 left brace, negative 10 less than "x" less than negative 9 , right bracey=9−10<x<−9
63
Expression 64: "y" equals StartRoot, 0.2 5 minus left parenthesis, "x" plus 9.5 , right parenthesis squared , EndRoot plus 9y=0.25−x+9.52+9
64
Expression 65: "x" equals negative 6.5 left brace, 0 less than "y" less than 7 , right bracex=−6.50<y<7
65
Expression 66: "x" equals negative 7.2 5 left brace, 0 less than "y" less than 7 , right bracex=−7.250<y<7
66
Expression 67: "y" equals 7 left brace, negative 7.2 5 less than "x" less than negative 6.5 , right bracey=7−7.25<x<−6.5
67
Expression 68: "y" equals StartRoot, 0.1 5 minus left parenthesis, "x" plus 6.8 9 , right parenthesis squared , EndRoot plus 7y=0.15−x+6.892+7
68
Expression 69: "x" equals 9 left brace, 0 less than "y" less than 9 , right bracex=90<y<9
69
Expression 70: "x" equals 10 left brace, 0 less than "y" less than 9 , right bracex=100<y<9
70
Expression 71: "y" equals 9 left brace, 9 less than "x" less than 10 , right bracey=99<x<10
71
Expression 72: "y" equals StartRoot, 0.2 5 minus left parenthesis, "x" minus 9.5 , right parenthesis squared , EndRoot plus 9y=0.25−x−9.52+9
72
Expression 73: "x" equals 6.5 left brace, 0 less than "y" less than 7 , right bracex=6.50<y<7
73
Expression 74: "x" equals 7.2 5 left brace, 0 less than "y" less than 7 , right bracex=7.250<y<7
74
Expression 75: "y" equals 7 left brace, 6.5 less than "x" less than 7.2 5 , right bracey=76.5<x<7.25
75
Expression 76: "y" equals StartRoot, 0.1 5 negative left parenthesis, "x" minus 6.8 9 , right parenthesis squared , EndRoot plus 7y=0.15−x−6.892+7
76
Expression 77: "y" equals negative 10absolute value left parenthesis, "x" minus 9.5 , right parenthesis plus 10.2 5 left brace, 9.4 2 less than "x" less than 9.5 8 , right bracey=−10absx−9.5+10.259.42<x<9.58
77
Expression 78: "y" equals negative 10absolute value left parenthesis, "x" plus 9.5 , right parenthesis plus 10.2 5 left brace, negative 9.5 8 less than "x" less than negative 9.4 2 , right bracey=−10absx+9.5+10.25−9.58<x<−9.42
78
Expression 79: "y" equals negative 10absolute value left parenthesis, "x" minus 6.9 , right parenthesis plus 8 left brace, 6.8 4 less than "x" less than 6.9 6 2 , right bracey=−10absx−6.9+86.84<x<6.962
79
Expression 80: "y" equals negative 10absolute value left parenthesis, "x" plus 6.9 , right parenthesis plus 8 left brace, negative 6.9 6 2 less than "x" less than negative 6.8 4 , right bracey=−10absx+6.9+8−6.962<x<−6.84